Jobsheet Sebagai Pemantik Pembelajaran Interaktif dalam Praktikum - Ahmad Pariyono; Cucuk Wawan Budiyanto; Muji Lestari (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2022)
Learning in the digital age requires upskilling and reskilling in the application to the efficacy of learner-centered learning. Every time that goes by and becomes a new era to always accompany the development of the times, especially in the world of education. So with the development of this Era, it is hoped that educators will be able to adjust to welcoming the learning of the Eras and Their Eras. So that true learning is created with enthusiasm and happiness will be obtained by students and educators to carry out meaningful learning activities according to the environmental conditions of each school. So it is necessary to hold a shift starting from reorganizing the mindset of learning puzzles, the mindset of fierce teachers, assertive teachers, teachers commanding, and learning focusing on the teacher that we must be aware of, so that students also have the space and time to grow in accordance with the era of their time. Most importantly learners get enough love and material for them to process to discover the natural potesntion that exists in each – each unique individual.